The pricing of loans to LBOs in the U.S. versus Europe - Machado, Daniela Fernandes (2020)
This thesis investigates the determinant factors concerning pricing of loans in LBOs, using a sample of 13,315 syndicated loans closed from 2000 to 2013. The results seem to indicate that spreads and pricing processes differ significantly in market-based versus bank-based financial systems as well as in the U.S. versus W.E. In the pre-crisis period, LBO loans extended to market-based borrowers face higher spreads compared to bank-based countries. During the crisis-period, borrowers from common law legal systems face higher spreads for loans in LBOs. The regression results presented for LBO loans extended to U.S. versus W.E. borrowers demonstrate that those in the U.S. face higher spreads. These results are in line with Carey and Nini (2007). A robust convex relationship between spread and maturity is found for loans in LBOs. Lastly, acquired firms with higher cash flow potential (market-to-book ratio) and asset tangibility (fixed asset to total assets) experience a lower spread. Furthermore, firms’ characteristics, namely book leverage, do not affect the pricing of loans in LBOs, opposed to marketability and default factors.